Atmospheric transmission and thermal background emission in the mid-infrared at Mauna Kea. (March 2015) - Otárola, A; Richter, M; Packham, C; Chun, M
Abstract: We present results of a preliminary study intended to quantitatively estimate the atmospheric transmission and thermal background emission in the mid-infrared (MIR), 7 μm - 26 μm, at the 13N TMT site in Mauna Kea. This is in the interest of supporting the planning of MIR instrumentation for the posible second-generation of astronomical instruments for the Thirty Meter Telescope (TMT) project. Mauna Kea, located at high altitude (4, 050 m above sea level), enjoys natural conditions that make it an outstanding location for astronomical observations in the mid-infrared. The goal of this work is to produce a dataset and model that shows the atmospheric transmission and thermal emission for two cases of precipitable water vapor (PWV), a low value of 0.3 mm, and at 1.5 mm which represent near median conditions at the site. Besides, and driven by the interest of the MIR community to exploit the daily twilight times, we look at the specific atmospheric conditions around twilight as a function of season. The best conditions are found for cold and dry winter days, and in particular the morning twilight offers the best conditions. The analysis of PWV data, shows the median value for the site (all year conditions between 6:00 PM and 7:30AM) is 1.8 mm and that periods of water vapor lower than 1.0 mm are common, these supports the opportunity and discovery potential of the TMT project in the mid-infrared bands.